Men who live alone have high risk of NOAC discontinuation. (25th November 2020) - Binding, C; Olesen, J.B; Lee, C; Sindet-Petersen, C; Pedersen, C.T; Gislason, G; Bonde, A
Abstract: Background/Introduction: Patients with atrial fibrillation (AF), who are considered at risk of stroke, are treated with oral anticoagulants (OACs), and non-vitamin K antagonist oral anticoagulants (NOACs) are preferred over vitamin K antagonists in recent guidelines. Poor NOAC compliance among patients with AF could result in an increased risk of thromboembolism and major bleeding, however, it has yet to be evaluated how cohabitant status and gender affects compliance with NOAC treatment among patients with AF. Purpose: The aim of this study was to evaluate the risk of NOAC discontinuation among patients with AF according to cohabitant status and gender. Methods: Using the Danish national registries we identified and included patients with AF aged 40–90 years in treatment with NOAC. The study period was from 2013 to 2017, and patients were followed for two years, or until death, outcome or emigration. The main outcome was discontinuation of NOAC-treatment for at least 30 days. Absolute risks were calculated as cumulative incidences using the Aalen Johansen estimator, and multiple covariate adjusted Cox regressions were used to calculate hazard ratios (HR). Results: We included 32, 380 patients with AF in NOAC treatment, where 16.8% were men living alone (median age 72 years), 25.8% were women living alone (median age 79 years), 37.2% were men living with a partner (median age 70 years), and 20.2% were women living with a partner (median age 79 years). Absolute two-year risk of NOAC discontinuation was highest among men living alone (Cumulative Incidence (CI) 0.19; 95% CI: 0.17 to 0.20), followed by men living with a partner (CI 0.18; 0.17 to 0.19), women living with a partner (CI 0.16; 0.15 to 0.17), and women living alone (CI 0.13; 0.12 to 0.14). After adjustment, living alone was associated with an increased risk of NOAC discontinuation among men (HR 1.15, 95% CI: 1.05 to 1.26), but not among women (HR 1.04, 95% CI: 0.93 to 1.15, interaction p=0.32). In an analysis evaluating gender, we found that being male was associated with a significantly higher risk of NOAC-discontinuation (HR 1.18, CI: 1.10 to 1.25) compared to women. Results were similar when we used 60 days discontinuation instead of 30 days discontinuation as outcome. Conclusion: Gender and cohabitant status was significantly associated with risk of NOAC discontinuation. Male gender and living alone was associated with a higher risk of NOAC discontinuation among patients with AF in a nationwide population. Funding Acknowledgement: Type of funding source: None